Disparitas Teknis dan Estetika: Analisis Komparatif Desain Pemenang Lomba Batik Tulang Bawang Barat - Ony Setyawan; Andi Irawan (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2025)
This study aims to describe and critique the visual presentation of ornamentation used in the 2025 Tubaba Signature Batik Design Competition. The analysis of visual ornamentation design in the form of batik motifs was conducted on the works of the first, second, and third-place winners of the competition. This study is grounded in the standardization of batik creation, specifically the characteristic ornamentation of batik pesisiran. This research employs a qualitative data collection method. Data analysis involves stages of data collection, data interpretation, and determining correlations between data points. The results indicate technical disparities and variations in aesthetic application by the designers, which impacted the fulfillment of various indicators used in the Tubaba batik competition assessment. The evaluation of these criteria is based on an investigation of batik pattern quality, motif clarity, and the alignment with the competition theme and regional identity. Furthermore, it considers the feasibility of the designs across various batik techniques—such as hand-drawn (batik tulis), stamped (batik cap), or a combination of both—as well as a symbolic-ornamental nature that is not overly symbolic.